PEMBANGUNAN BERKELANJUTAN BERBASIS KEADILAN SOSIAL DI KABUPATEN GORONTALO - Harijono Imbran; Ramlah Alaktiri (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
Sustainable development remains a strategic issue that continues to be widely discussed, particularly following the enactment of Presidential Regulation Number 59 of 2017 concerning the Implementation of the Sustainable Development Goals (SDGs). However, the implementation of this policy, especially at the regional level, has not yet been optimal and tends to lack clear direction, particularly in the social dimension. Gorontalo Regency demonstrates relatively strong economic development, as indicated by an economic growth rate that exceeds the national average. Nevertheless, this economic growth has not been accompanied by equitable income distribution, resulting in persistent social inequality, which contradicts the fundamental principles of sustainable development. This study aims to examine the actual conditions of sustainable development in Gorontalo Regency from a social dimension perspective. A descriptive qualitative research approach is employed to capture the empirical realities of development and to provide insights for future policy formulation. The findings reveal that the average economic growth rate of 5.01 percent over the past five years reflects positive regional economic performance; however, maximizing the benefits of this growth requires greater attention to social justice. Therefore, inclusive and sustainable development policies are needed through improved access to education, healthcare, and infrastructure, as well as increased community participation in development planning and implementation, to ensure that development benefits are equitably distributed across all segments of society in Gorontalo Regency